Television, nation, and culture in Indonesia - Kitley, Philip, 1946- (Research in international studies. Southeast Asia series ;, 2000)
The culture of television in Indonesia began with its establishment in 1962 as a public broadcasting service. From that time, through the deregulation of television broadcasting in 1990 and the establishment of commercial channels, television can be understood, Philip Kitley argues, as a part of the New Order's national culture project, designed to legitimate an idealized Indonesian national cultural identity. But Professor Kitley suggests that it also has become a site for the contestation of elements of the New Order's cultural policies. Based on his studies, he further speculates on the.